Integrated Cross Sections of the Photo-Neutron Reactions Induced on \(^{197}\)Au with 60 \(\text{MeV}\) Bremsstrahlung - Do, Nguyen Van; Luan, Nguyen Thanh; Xuan, Nguyen Thi; Khue, Pham Duc; Thanh, Kim Tien; Loat, Bui Van; Hien, Nguyen Thi; Kim, Guinyun (Communications in Physics, 2020)
Abstract. Seven photo-neutron reactions 197Au(γ,xn)197-xAu (with x=1-7) produced by the bremsstrahlung end-point energy of 60 MeV were identified. In this work, we focus on the measurement of integrated sections. Experiments were carried out based on the activation method in combination with off-line gamma-ray spectrometric technique. The integrated cross sections of the investigated reactions were determined relative to that of the monitoring reaction 197Au(γ,n)196Au. To validate the experimental results, theoretical predictions were also made using the computer code TALYS 1.9. The current integrated cross-sections of the 197Au(γ,xn)197-xAu reactions with 60 MeV bremsstrahlung end point energy are measured for the first time.